TEACHER’S EFFORTS IN OVERCOMING PAI LEARNING DIFFICULTIES JUDGING FROM THE LEARNING STYLES OF STUDENTS AT SMA PATRA MANDIRI 01 PALEMBANG - Aprina, Marni Prasyur (Indonesian Journal of Educational Development (IJED), 2023)
Learning difficulties can occur if the teacher is not qualified in taking learning methods. Therefore, teachers need to facilitate learning in the classroom according to the learning styles of students. This study aims to determine the learning difficulties experienced by students as well as complement previous studies on the efforts that teachers can make in overcoming these difficulties. This type of research is a case study. Data collection techniques use observation, interviews and documentation. Data validity techniques use triangulation techniques. The results showed the form of PAI (Pendidikan Agama Islam) learning difficulties of visual students in the form of difficulty reading the Qur'an and slow to understand learning material, auditory students namely difficulty reading the Qur'an, difficulty writing Arabic letters, and slow in memorization, and kinesthetic students namely difficulty reading the Qur'an and slow in memorization. The efforts of PAI teachers in overcoming visual learners' learning difficulties are using audio-visual learning media when explaining material and marking important things with color variations. To overcome the learning difficulties of auditory students, namely using audio-visual learning media when explaining learning material, inviting students to read aloud, and using discussion methods and group assignments. Meanwhile, to overcome learning difficulties, kinesthetic learners are doing practice.